Effectiveness of Training on Uptake of Continuous Professional Development among Nurses and Midwives in Clinical Practice - Meru County, Kenya - Odhiambo, Roselyne Akinyi; Marwa, Immaculate Nyaseba; Gitonga , Lucy Kawira (International Journal of Professional Practice, 2024)
Continuous Professional Development refers to the process by which members of a profession broaden their knowledge and competence to acquire professional qualities required in the practice. In Sub-Saharan Africa, the need for nurses and midwives is increasing. In Meru County, the Maternal Mortality Rate remains a burden. To bridge the gap between knowledge and practice, the Nursing Council of Kenya, in line with the International Confederation of Midwives, requires nurses and midwives to complete 20 hours of CPD annually, promoting continuing education programs. This study is a follow up of phase one study carried out to assess factors that influence uptake of CPD among nurses and midwives in Meru County, Kenya. The objective of the study was to assess the effectiveness of training on uptake of CPD in clinical practice. This was a quantitative study that adopted randomized controlled trial design, utilizing the participants of the phase one study. A total of 70 nurses and midwives from the sampled participants were randomly allocated to the intervention and control groups using systematic random sampling technique. Training was conducted based on the findings of the phase one study. At the beginning of the training, all the participants (n=70) did a pretest, and a post test at the close, with participants from the intervention group being trained. This enabled the researcher to assess the effect of training on participant’s knowledge and skills. Data was analyzed using SPSS version 26. Results showed great improvement in knowledge and skills with a pretest mean of 54.19% and a posttest mean of 90%. The paired t-test value was highly statistically significant (p < .001, 95% CI). To enhance a more organized and regularized way of CPD provision, the study developed a CPD Model.